An Interactive Book With Augmented Reality For Learning The Cirebon Mask Dance - Dinan Yulianto; Rudy Hartanto; Paulus Insap Santosa (JURNAL INFOTEL, 2018)
Today, augmented reality has an important role in human activity, especially in the field of education. The increasing capabilities of mobile devices also contribute to augmented reality to reduce real world distance with the virtual world. This paper will discuss the design and testing of iBook as media of learning the Cirebon mask dance art. IBook is a form of optimisation of traditional books based on augmented reality. The iBook designs will interact with virtual objects through direct touch on the application interface (pinch and swipe). The technical testing of iBook is a test of marker less reading ability and audio response time test. The markerless detection test resulted in minimum response time less than 1 second, minimum distance of 64 cm and a maximum distance of 3 cm, a minimum angle of 23° and a maximum angle of 90°. Tracking test obtained a minimum distance of 3 cm and a maximum distance of 71 cm, a minimum angle of 90° and a maximum angle of 16°. Any markerless detection and tracking can be done in unobstructured condition of no more than 50%. The testing of audio content obtained activation response time less than 1 second with original duration equal to active duration.